Post a New Question

algebra 2

posted by .

write the general form of
f(x)=4(x-1)^-8
(x-1) (x-1)=
4(x^-2x+1)-8
4x^-2x-8

  • algebra 2 -

    Use a number with exponents.

    4(x-1)^2 - 8
    4(x^2-2x+1)-8
    4x^2-8x+4-8
    4x^2-8x-4

    You must multiply the 4 by each term in the parentheses, not just the first one.

    4(2+6) = 4*2 + 4*6 = 8+24 = 32
    NOT
    4(2+6) = 4*2+6 = 8+6 = 14

    after all, 2+6=8, and 4*8 = 32

  • algebra 2 -

    f(x) = 4(x-1)^2 - 8
    = 4(x^2 - 2x + 1) - 8
    = 4x^2 - 8x + 4 - 8
    = 4x^2 - 8x - 4

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question